국내에서 분리된 Streptomycin 저항성 Pseudomonas syringae pv. actinidiae Biovar 3 균주에서 rpsL 유전자의 돌연변이 - 이영선(Young Sun Lee); 김경희(Gyoung Hee Kim); 고영진(Young Jin Koh); 정재성(Jae Sung Jung) (Sigmulbyeong yeon'gu, 2022)
Pseudomonas syringae pv. actinidiae (Psa) is the causal agent responsible for the bacterial canker disease of kiwifruit plants. Psa strains are divided into five different biovars based on genetic and biochemical characteristics. Among them, biovar 2 and 3 strains of Psa were isolated and have been causing widespread damages in Korea. One of the most effective ways to control Psa is to use an antibiotic such as streptomycin. However, Psa strains resistant to this antibiotic were isolated in Korea, and an earlier study revealed that the resistance in the biovar 2 is associated with strA-strB genes. This study aimed to determine the molecular resistance mechanism of Psa biovar 3 strains to streptomycin. Sequencing the rpsL gene encoding ribosomal protein S12 from three streptomycin-resistant strains screened in the laboratory revealed that a spontaneous mutation occurred either at codon 43 or 88. Meanwhile, in four streptomycin-resistant strains of Psa biovar 3 isolated from two kiwifruit orchards, a single nucleotide in codon 43 of the rpsL, which is AAA in streptomycin-sensitive strain, was substituted for AGA causing an amino acid change from lysine to arginine. The resistant mechanism in all biovar 3 strains obtained in Korea was identified as a mutation of the rpsL gene. Pseudomonas syringae pv. actinidiae (Psa)는 키위에 세균성 궤양병을 일으키는 병원균이다. Psa 균주는 유전적 및 생화학적 특징에 따라 5개의 biovar로 나누어진다. 그중 biovar 2와 3이 국내에서 발견되어 광범위한 피해를 주고 있다. Psa를 방제하는 효율적인 방법 중 한가지는 streptomycin과 같은 항생제를 사용하는 것이다. 그러나, 이 항생제에 저항성을 갖는 균주가 국내에서 분리되었고, 선행 연구에서 biovar 2 균주의 저항성이 strA-strB 유전자에 의한 것으로 밝혀졌다. 본 연구에서는 Psa biovar 3 균주에서 streptomycin 저항성의 분자적 기작을 밝히고자 하였다. 실험실에서 선발된 streptomycin 저항성 균주의 리보솜 단백질 S12를 암호화하는 유전자인 rpsL의 염기서열을 결정한 결과, 43번째 또는 88번째 코돈에서 자연발생적 점 돌연변이가 일어난 것을 확인하였다. 한편, 두 곳의 키위 과수원에서 분리된 4개의 streptomycin 저항성 biovar 3 균주에서는 민감성 균주에서 AAA인 rpsL의 코돈 43이 AGA로 단일 염기 치환이 일어났고, 이는 아미노산을 lysine에서 arginine으로 변화시키게 된다. 국내에서 발견된 biovar 3 균주 모두의 저항성 기작은 rpsL 유전자의 돌연변이에 기인하였다.